2010
DOI: 10.1021/ic1015127
|View full text |Cite
|
Sign up to set email alerts
|

Isomorphous Substitutions of Rare Earth Elements for Calcium in Synthetic Hydroxyapatites

Abstract: Polycrystalline hydroxyapatites Ca(10-x)REE(x)(PO(4))(6)(OH)(2-x)O(x) were synthesized and studied by X-ray powder diffraction, infrared absorption, diffuse-reflectance spectroscopy, and thermogravimetry. The solubility limits x(max) of rare earth elements (REE) in Ca hydroxyapatites decreases with an increasing REE atomic number from x(max) = 2.00 for La, Pr, and Nd to x(max) = 0.20 for Yb at 1100 °C. Refinements of X-ray diffraction patterns by the Rietveld method show that REE atoms substitute for Ca prefer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(23 citation statements)
references
References 56 publications
0
22
0
1
Order By: Relevance
“…the ionic radius of Nd 3+ , 1.25 (CN = 8), matches within 1% to that of Ca 2+ . Substitution rates of REEs for Ca 2+ in the bioapatite lattice are governed by differences in crystal lattice strain [31], [32]. Metastable bioapatite nanocrystals tend to dissolve and recrystallise until the bone possibly reaches a relatively close-pore state.…”
Section: Resultsmentioning
confidence: 99%
“…the ionic radius of Nd 3+ , 1.25 (CN = 8), matches within 1% to that of Ca 2+ . Substitution rates of REEs for Ca 2+ in the bioapatite lattice are governed by differences in crystal lattice strain [31], [32]. Metastable bioapatite nanocrystals tend to dissolve and recrystallise until the bone possibly reaches a relatively close-pore state.…”
Section: Resultsmentioning
confidence: 99%
“…Oxygen K-ELNES for HA was simulated using experimental structure parameters obtained from xray diffraction studies [85]. Since partial occupancy is not possible in explicitly atomistic simulations, a random structure program was utilized to populate two of the four possible hydroxide positions to remove investigator bias [86].…”
Section: Oxygenmentioning
confidence: 99%
“…For example, for the Zhijin Xinhua rare earth phosphate deposits in western China (the largest rare earth resources reserve of phosphate rock [10]), the average grade of rare earth oxide (REO) is 0.05% to 0.13%, and La, Ce, Nd and Y account for 81.20% of the total REOs [11]. Test data [12,13] showed that REEs replace calcium mainly in the form of isomorphism in the phosphate rock (mainly fluorapatite or carbonate-fluorapatite). Although the apatite and dolomite or calcite contain the same element Ca in crystals, the REEs can be only displaced into the apatite lattice rather than the dolomite or calcite, and there is no relevant explanation for that.…”
Section: Introductionmentioning
confidence: 99%